2020
DOI: 10.1109/access.2020.3033472
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Wearable EEG Systems Using Functional Connectivity

Abstract: Assessing the data quality of wearable electroencephalogram (EEG) systems is critical to collecting reliable neurophysiological data in non-laboratory environments. To date, measures of signal quality and spectral characteristics have been used to characterize wearable EEG systems. We demonstrate that these traditional measures do not provide fine-grained differentiation between the performance of four popular wearable EEG systems (the Epoc+, OpenBCI, DSI-24 and Quick-30 Dry EEG). Using two computationally ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Then, EEG segments were exported in a custom MATLAB plug-in EEGapp (EEGapp, BIAPT lab, McGill University) for analysis. 46 …”
Section: Methodsmentioning
confidence: 99%
“…Then, EEG segments were exported in a custom MATLAB plug-in EEGapp (EEGapp, BIAPT lab, McGill University) for analysis. 46 …”
Section: Methodsmentioning
confidence: 99%
“…However, as might be expected, consumer-grade devices display considerably poorer signal-to-noise ratios than their research-grade counterparts. Mahdid et al [139] found that the functional connectivity of both Emotiv and OpenBCI systems compared poorly to researchgrade systems; Raduntz [140] found that the signal reliability of Emotiv was poor if the device did not exactly fit the participant's head; and Ekandem et al [141] observed that the signal quality of an Emotiv (specifically, the EPOC+) declines over time as it uses a built-in rechargeable battery. There were few validation studies for the remaining devices.…”
Section: Validationmentioning
confidence: 99%
“…Methods can rely on human intervention [27] or be (semi)automated. Representative examples of the latter include methods that rely on data statistics (e.g., [28,29]), spectral/connectivity profiles (e.g., [30][31][32]), blind source separation (e.g., [33,34]), adaptive filtering (e.g., [35,36]), and, more recently, on machine and deep learning approaches (e.g., [37][38][39][40]). Combinations of multiple such approaches have also been proposed (e.g., [41,42]).…”
Section: Introductionmentioning
confidence: 99%